Pengaruh Penggunaan Model Pembelajaran Active Learning (SAVI) terhadap Kemahiran Berbicara Bahasa Arab - Rosdiana Djahibakal (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
This study aims to examine the effect of implementing the SAVI (Somatic, Auditory, Visual, Intellectual) active learning model on improving Arabic speaking skills (Mahārah al-Kalām) among 11th-grade students at MAN Alor NTT. A quantitative method with a pre-experimental design (One-Group Pretest-Posttest Design) was employed. The sample consisted of 30 students selected through purposive sampling. Data were collected through oral tests (pre-test and post-test), active participation observations and documentation. Test data were analyzed using the Independent Samples T-Test and normalized gain (N-Gain) tests, while observational data were analyzed using percentage descriptive statistics. Data were analyzed using the Shapiro-Wilk normality test and the Paired Sample t-Test via SPSS. The results showed a significant improvement in students' speaking skills following the implementation of the SAVI model. The mean score increased by 24.17 points, from 58.33 in the pre-test (low/fair category) to 82.50 in the post-test (good/high category). Hypothesis testing revealed a calculated -value of 27.46, exceeding the -table value () with a significance value of , leading to the rejection of and acceptance of . Thus, it can be concluded that the SAVI active learning model has a positive and significant effect on the Arabic speaking skills of students at MAN Alor NTT.